Design and fabricate a reer wheel drive differential simulation rig - Dinnish, A/L Thegaraju (2008)
Design and fabricating the rear wheel drive differential simulation rig is a conceptual understanding of automotive engineering which is not provided in daily lectures room due to the fact that it is advance knowledge in this field. The project gives awareness of what is going on inside a differential by showing it to people using a rig As such, it is vital to attain this basic knowledge through this project. The purpose of this project is to design, fabricate a rear wheel drive differential simulation rig. The design is purely new and the idea is generated by other types of simulation rig. Material that is strong and could withstand the weight and the vibration of moving parts of the rig. Tests have been done to ensure the rig has meet the objective stated. The progress of this project needs documenting, as it can be a good reference for the next student who involve in this project as well as for a research related to the differential simulation rig. This report describes the project development of the first prototype of UMP rear wheel drive differential simulation rig.